2024
DOI: 10.1002/bse.3672
|View full text |Cite
|
Sign up to set email alerts
|

How does digitization enable green innovation? Evidence from Chinese listed companies

Wen Chen,
Changyi Zhu,
Qi Cheung
et al.

Abstract: The coordinated development of digitization and greening is an essential requirement for the sustainable development of the global economy. With the rapid development of the digital economy, enterprises are facing a new external environment for green innovation. This paper uses the robust principal component analysis method to construct the digital economy development index for Chinese prefecture‐level or above cities from 2012 to 2019 and examines the impact of the digital economy on corporate green innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…The authors found that digital transformation improves innovation performance by enhancing the strategic agility of enterprises [37]. Enterprise digital transformation enhances green innovation by easing financing constraints, reducing agency costs, and stimulating growth potential [38]. Not only that, digital transformation improves corporate ESG performance through environmentally friendly digital technology and becomes a "technical reservoir" that supports green development [39].…”
Section: Digital Transformationmentioning
confidence: 99%
“…The authors found that digital transformation improves innovation performance by enhancing the strategic agility of enterprises [37]. Enterprise digital transformation enhances green innovation by easing financing constraints, reducing agency costs, and stimulating growth potential [38]. Not only that, digital transformation improves corporate ESG performance through environmentally friendly digital technology and becomes a "technical reservoir" that supports green development [39].…”
Section: Digital Transformationmentioning
confidence: 99%
“…By leveraging economies of scale, economies of scope, and other factors, the digital economy is capable of reducing the cost of information communication [ 16 , 17 ] and enhancing production efficiency [ 18 , 19 ], thereby stimulating GI [ 20 , 21 ]. Externally, the advancement of the digital economy can bolster companies’ green innovation through various means, such as boosting economic openness, optimizing industrial structure, expanding market potential, increasing media visibility, and reducing environmental uncertainty [ 6 , 14 , 22 , 23 ]. Internally, digital progress can drive green innovation by refining human capital structures, easing financial constraints, enhancing internal controls, strengthening human capital, and fostering the enhancement of the enterprise value chain [ 5 , 24 , 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the deep integration of digital empowerment and the real economy can help accelerate the digital transformation of industry. In particular, digital empowerment has become a key engine for companies to access new opportunities and paths for growth [ [4] , [5] , [6] ]. According to the Digital China Development Report (2022) released by the National Internet Information Office, China's digital economy is 50.2 (7.2) trillion yuan (dollars) in 2022, ranking second in the world.…”
Section: Introductionmentioning
confidence: 99%